Mobile App for Science Education: Designing the Learning Approach - Rita Tavares; Rui Marques Vieira; Luís Pedro (MDPI AG, 2021)
This paper reports research work related to a wider study, aimed at developing a mobile app for Science Education in primary-school. Several studies reveal that Science Education can be improved by using technology, namely educational software. However, to promote a structured use of technology, innovative learning approaches must be designed for educational software. This paper aims to answer how the interaction between students and a mobile app for Science Education can promote students' scientific competences development and self-regulated learning. To achieve this, a learning approach was designed, combining the Universal Design for Learning principles, Inquiry-Based Science Education and the BSCS 5E - teaching model for Science Education designed by the Biological Sciences Curriculum Study, which results in the acronym of the model. The 5E is related to each phase of the model: Engagement; Exploration; Explanation; Elaboration; Evaluation. The proposed was based on a grounded, participatory, and user-centred approach, crossing literature contributions with data collected among primary-school teachers through the application of a questionnaire (n = 118). Data collected allowed deductions about the expected adequacy of the learning approach, according to Nieveen's criteria for high quality educational interventions. This adequacy was revealed through the teachers' conceptions about the potential impact of the conceptualized mobile app (i) to provide a comprehensive and practical Science Education learning; and (ii) to enhance students' scientific competences development and self-regulated learning. The paper aims to contribute to the design of an innovative learning approach in Science Education and to share it with other researchers since it can be expanded to other educational software.